2017
DOI: 10.18632/oncotarget.21490
|View full text |Cite
|
Sign up to set email alerts
|

Breast tissue, oral and urinary microbiomes in breast cancer

Abstract: It has long been proposed that the gut microbiome contributes to breast carcinogenesis by modifying systemic estrogen levels. This is often cited as a possible mechanism linking breast cancer and high-fat, low-fiber diets as well as antibiotic exposure, associations previously identified in population-based studies. More recently, a distinct microbiome has been identified within breast milk and tissue, but few studies have characterized differences in the breast tissue microbiota of patients with and without c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
171
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(189 citation statements)
references
References 67 publications
14
171
4
Order By: Relevance
“…1 The largest study to examine microbes and BC was from The Cancer Genome Atlas (TCGA) wherein Proteobacteria, Actinobacteria, and Firmicutes were shown as the most abundant phyla in breast tumors, which is consistent with our work and others, and reminiscent of the gut. 1,11,14,18,21,168,[172][173][174][175][176]180,181 We detected dysbiosis in breast tumors and tumor-adjacent breast tissue compared to normal tissue from healthy subjects. Recall that Ruminococcus is high in the gut of BC patients 11 and reduced by Mediterranean diet in the mammary glands of monkeys.…”
Section: While Tumors Had Lowermentioning
confidence: 87%
See 1 more Smart Citation
“…1 The largest study to examine microbes and BC was from The Cancer Genome Atlas (TCGA) wherein Proteobacteria, Actinobacteria, and Firmicutes were shown as the most abundant phyla in breast tumors, which is consistent with our work and others, and reminiscent of the gut. 1,11,14,18,21,168,[172][173][174][175][176]180,181 We detected dysbiosis in breast tumors and tumor-adjacent breast tissue compared to normal tissue from healthy subjects. Recall that Ruminococcus is high in the gut of BC patients 11 and reduced by Mediterranean diet in the mammary glands of monkeys.…”
Section: While Tumors Had Lowermentioning
confidence: 87%
“…167 Examination of the local microbiome in BC compared to normal tumor-adjacent or normal mammary gland has revealed interesting alterations. 11,14,168,[172][173][174][175][176] The Western diet is associated with obesity and poor tumor outcomes. 177 Cook et al showed for the first time that Mediterranean vs Western diet could alter mammary gland microbes, specifically increasing Lactobacillus by 10-fold and reducing Ruminococcus in the mammary gland of non-human primates.…”
Section: Crob E S In E X Tr A-inte S Tinal Tissue and C An Cermentioning
confidence: 99%
“…In this regard, it has been proposed that certain gut microbes may play a role in breast carcinogenesis by promoting antitumor immunity and immune surveillance, and/or by modulating systemic estrogen levels [44,45]. BC associations with estrogen levels could reflect differences among individuals in their intestinal microbial communities [46], as shown 50 years ago by Adlercreutz and collaborators, who demonstrated one of the fundamental roles of the gut microbiota [47].…”
Section: Gut Microbiotamentioning
confidence: 99%
“…Although habitual physical activity is thought to modulate this relationship (McTiernan et al., ), it is unclear whether the benefits of physical activity are driven by changes in adiposity or gut microbiota, because both are associated with systemic oestrogens. Recent comparative analyses of microbiota from urine and local breast tissue (Wang et al., ), in addition to gut microbes (Goedert et al., ), have revealed compositionally distinct microbiomic profiles between women with and without breast cancer. Thus, a complex interaction exists between gut microbiota diversity, adiposity, menopausal status and free‐living physical activity.…”
Section: Introductionmentioning
confidence: 99%